(untitled) (Functional Plant Breeding Journal, 2021)
This article aims to evaluate the anti-inflammatory potential of Mandacaru (C. jamacaru), through a literature review. The research was carried out through a bibliographic review based on technical books and articles selected in several databases such as Google Scholar, Medline, SciELO and electronic health journals. For the study, the following descriptors were applied: anti- inflammatory action, Cereus jamacaru, mandacaru, herbal medicine. The electronic research was based on studies published with no year limit of publication. In the research articles were obtained citing works carried out in almost all the states of the Brazilian Northeast. In these, it was observed that the most used parts of the plant are the stalk and the root, with the decoction being the most used therapeutic form. Several forms of inflammation have been cited, however the one that stood out most for the kidneys. Experimental research has indicated the presence of amines (tyramine and N-methylthyramine), terpenes, steroids, flavonoids, phenolic acids, among other chemical compounds, being a potent antibacterial and practically non-toxic